Theoretical and practical flebotomy skills among first-semester medicine students at the Montagne Simulation Center, Mérida - México - Cetina-Sauri, Gregorio (2018)
Introduction. The use of human patient simulators is an effective strategy in the teaching of clinical procedures. However, there is little information to help teachers improve their teaching strategies, allowing them to improve learning experiences according to the age or sex of students who use this type of simulation. Objectives. To identify if there are differences by sex or age in association with the skills of the students of the first semester of medicine for phlebotomy. Design. Quasiexperimental. Places. Medical Simulation Centre Montagne of the Marista University of Merida. Participants. First semester medical students. Interventions. Educational intervention of the phlebotomy process with sample taking, and using high fidelity simulators. For the analysis, sociodemographic variables were associated with the performance of the students. Main result measures. The practical and theoretical evaluations were analyzed. For the practical evaluation, a rubric of 20 items was applied and the scores of the theoretical and practical areas of the students were averaged. Results. It was identified that women performed their practical skills better (p <0.03) even in the linear regression model adjusted for age and group. Discussion. The best performance in the practice of phlebotomy among medical students is hardly an isolated finding, since they could derive from the skills for interpersonal communication, which can also be reinforced in male students.